Association of muscle-specific creatine kinase (CKM) gene polymorphism with combat athlete status in Polish and Russian cohorts - Fedotovskaya, O.; Eider, J.; Cieszczyk, P.; Ahmetov, I.; Moska, W.; Sawczyn, S.; Leonska-Duniec, A.; Maciejewska-Karlowska, A.; Sawczuk, M.; Czubek, Z.; Zychowska, M.; Jascaniene, N. (Archives of Budo, 2013)
Combat sports are characterized by the involvement of both aerobic and anaerobic metabolic pathways in which the effort is of intermittent characteristics and explosive type of movements are repeated over time at high intensity. The A/G polymorphism (rs8111989) of the muscle specific creatine kinase (CKM) gene, encoding the protein which plays a key role in energy homeostasis of muscle cells, has been associated with physical performance. Specifically, the CKM G allele has been reported to be linked with power athlete status, whilst the CKM A allele has been significantly over-represented in endurance athletes. The aim of our study was to investigate the association between the CKM A/G polymorphism and combat athlete status in Polish and Russian cohorts. Material and Methods: The study was carried out in 159 combat athletes and 1512 sedentary individuals from Poland and Russia. DNA was extracted from buccal cells donated by the subjects and genotyping was carried out using PCR based methods. Results: We found that the frequency of the CKM G allele was significantly higher in the combined cohort of Polish and Russian athletes compared with controls (41.2 vs. 35.6%, P = 0.047). Conclusions: The results suggest that the CKM gene is associated with combat athlete status in Polish and Russian populations. Although more replication studies are needed, the preliminary data suggest an opportunity to use the analysis of CKM polymorphism along with other gene variations and standard phenotypic assessment in combat sports selection